White Turrets - Molesworth, Mrs., 1839-1921; Rainey, W. (William), 1852-1936 (Salt Lake City, UT : Project Gutenberg, 2013)
"White Turrets" by Mrs. Molesworth is a novel written in the late 19th century. Set against the backdrop of London, the story revolves around two sisters, Winifred and Celia Maryon, who embark on their first visit to the city, filled with aspirations and ideas about finding their place in a bustling society. As they navigate their new surroundings, they encounter other characters, including the singer Hertha Norreys, who captivates them and ignites discussions about ambition, personal development, and the societal expectations placed on women. The opening portion of the novel introduces a charity concert that sets the stage for the sisters' adventure and highlights their admiration for the singer, Hertha Norreys. Winifred, the elder sister, appears particularly taken by Hertha's performance, which signifies the beginning of her aspirations for something greater than a conventional life. Their interactions with other characters at the concert, including conversations about their contrasting views on women$1 (Bs roles, provide a glimpse into the themes of ambition, societal norms, and the quest for identity that will likely be explored further in the narrative. As the sisters intertwine with the lives of other characters, especially Hertha, their journey unfolds, exploring the balance between personal dreams and the expectations of their societal roles. (This is an automatically generated summary.)s
Release date is 2013-07-06
Produced by Nick Hodson of London, England
Keywords: England -- Social life and customs -- 19th century -- Fiction; Young women -- Fiction